Venous Anastomosis for Prevention of Venous Congestion in Distally Based Flaps - Jun Ihara, MD; Nobuaki Imanishi, MD; Kazuo Kishi, MD (Plastic and Reconstructive Surgery, Global Open, 2017)
Background:. Distally based flaps are useful for the treatment of skin defects of the extremities. However, congestion in the peripheral part of the flap due to reverse flow can cause partial flap necrosis. Previously, we reported on the effectiveness of venous anastomoses to rescue peripheral congestion of distally based flaps and applied this idea in a clinical setting. In this report, we present clinical cases of distally based flaps with venous supercharge anastomoses for changing the reverse venous flow into physiological flow, thereby reducing venous congestion. Methods:. Four patients with skin defects of the extremities (2 cases with defects of the knee and the upper third of the lower leg, 1 case of the lower third of the lower leg, and 1 case of the distal third of the forearm) were treated with local flaps (2 cases with distally based greater saphenous venoadipofascial sartorius muscle combined flaps, 1 case with a distally based lesser saphenous venoadipofascial flap, and 1 case with a distally based ulnar artery perforator flap). In each reconstruction, 1 or 2 veins in the flaps were anastomosed with superficial veins in the recipient area to change the reverse venous flow into a normal, physiologic flow. Result:. All flaps healed completely without any obvious venous congestion or flap necrosis. The coverage quality provided by these defects was satisfactory. Conclusions:. Adding venous anastomoses may reduce the risk of venous congestion and improve the outcomes of the distally based flaps.